Industrial process control systems - Patrick, Dale R. (Fairmont Press, 2009)
"Manufacturing deals with the transformation of materials into marketable products. A number of individual processes unique to the product being manufactured are generally grouped into systems which accomplish specific manufacturing operations. Systems that respond to temperature, pressure, flow level, and analytical procedures are commonly used in an industrial setting to manufacture a product. In this book, the systmes concept will serve as the basic approach to understanding and effectively applying industrial process control. Topics covered include the operating system, process control, pressure systems, thermal systems, level determining systems, flow process systems, analytical process systems microprocessor systems, automated processes and robotic systems."--Pub. desc